P20 Technical advances in imaging guided minimally invasive post-mortem CT angiography. (21st September 2022) - Xie, Cheng; MacKinnon, Tina; Cox, Peter; Thomas, Sheena; Galuppi, Giacomo; Kuttappan, Sathees; Freeman, David; Traill, Zoe; Fryer, Eve; Roberts, Ian; Antoniades, Charalambos
Abstract : Objective: Post-mortem computed tomography (PMCT) is widely used to reduce the requirement for invasive autopsy. The angiographic aspect of the PMCT has been described in centres in England and Europe using different techniques. This study was built on this foundation to develop an alternative approach by adopting interventional techniques under both ultrasound and CT guidance to achieve diagnostic PMCTAs and further preserve the integrity of the body. Methods: This prospective study was conducted after the approval of the ethics committee. Sudden adult deaths of unknown cause referred for Coroner's autopsy were recruited. The participants had PMCTA of the coronary arteries with our minimally invasive interventional techniques prior to autopsy (the technique will be described in detail). Results: All the ten participants underwent successful PMCTA. The participants' age ranged between 49 to 81 years old and passed away from both coronary and non-coronary related cause of death. Radiologist assessment of coronary artery disease (CAD) on PMCTA versus pathologist autopsy showed 83% concordance (25/30 coronary arteries) with Cohen Kappa coefficient 0.67. CAD severity scores (0 = normal, 1 = mild, 2 = moderate, 3 = severe) between the radiologist and pathologist were non-significant overall (P-value = 0.21), and artery specific (LAD P-value = 0.56; LCx P-value = 0.32; RCA P-value = 0.32). Conclusion: This minimally invasive imaging guided technique is able to achieve diagnostic quality PMCTA of the coronary arteries to investigate coronary related cause of death.